THE DEVELOPMENT OF TEACHING MATERIALS ON TOIEC READING FOR IMPROVING A MINIMUM SCORE STANDARD THROUGH THE ANALYTICAL SKILL ON QUESTION ITEMS - Siti Maisaroh; Sutarman Sutarman; Nunung Nurmaesah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Students at STMIK Bina Sarana Global is given TOEIC as one of compulsory subjects. However, after four years since TOIEC was taught, students had not significantly improved both their analytical skill of the question items as expected and in the targeted minimum score as to be achieved. The teaching materials have undergone changes for three times. Nevertheless, students still find the textbooks hard to understand, resulting in the low score students gained, particularly in the Reading section. This research is aimed at designing teaching materials to assist students in developing their analytical skill, with ADDIE as its research Method. ADDIE which encompasses five phases – Analysis, Design, Development, Implementation, and Evaluation became the basis analytical skill from which this in-depth research was conducted. The TOEIC Reading Skills textbook provides the content of units, which commences from the warm up activity, followed by topic explanation, to practice tests and word lists. Twenty students as the subjects of this research and a group of 6 lecturers served as evaluators whom were involved for the purpose of giving more thorough analyses towards the book content. Implementing mixed-method research in the data collections and analyses, the development of the teaching materials has been proven to be valid, effective, and practical. Students felt at ease comprehending the explanation, grew their interest in relation to the teaching materials and performance well on the practice test. As a result, they have shown significant improvement in sharpening their analytical skill towards the Reading question items and in obtaining a higher score. These were proven from the Post-Test, class discussions, interview, and questionnaire results.